Tingkat Kepatuhan Wajib Pajak Badan Usaha Mikro Kecil dan Menengah Setelah Diberlakukan Tarif 1 % (Final) PPh (Studi Kasus di KPP Pratama Pontianak) - Zawitri, Sari; Yuliana, Elsa Sari (Fakultas Ekonomi dan Bisnis, UNTAN, 2016)
Year 2015 is the year for developing Tax Payer and the year of issuance of GovernmentRegulation No. 46 Year 2013, which imposed 1% tax to SMEs with a turnover (gross income)from Rp 1 to a maximum of Rp 4.8 billion per year. The research problems are formulated: (1)How does the level of tax compliance in KPP Pratama Pontianak before and after the 1% taxpolicies for SME corporate tax payer? (2) What efforts made by the tax authorities in improvingtax payer compliance company in terms of delivering the tax obligations on KPP PratamaPontianak. The research method was an exploratory, descriptive, narrative case study approachto the object KPP Pratama Pontianak. Outcomes of this study are expected KPP PratamaPontianak be an example or reference for other KPP in performing their duties and functions aspublic service on tax. The results showed that there was a slight increase tax payer compliance inKPP Pontianak after their policy of 1% per month tax on turnover (gross income), whencompared with the prior policy. Suggestions for the government, in this case the DirectorateGeneral of Taxation, in formulating tax policy in order to maximize tax revenue.